Hyperbaric 0.5% Bupivacain used in subarachnoid block which spread of anesthesia to cephalic at the different site of injection specially L 2-3, L 3-4, L 4-5 inter vertebral space - Azad, AK; Taher, SMA; Raihan, Jamil; Zahid, M Abu; Rahman, Mahbubur; Alam, M Intekhab (TAJ: Journal of Teachers Association, 2018)
75 (18-45 years) caesarean section were done in RMCH from 2015 July to 2015 December, who received Hyperbaric 0.5% Bupivacain 2.5 ml at the site of L 2-3, L3-4 and L 4-5 inter vertebral spaces. All patients used 25 gauze spinal Needles after 5 & 10 minutes analgesia effect at the level of T10 and T6 respectively. But analgesia effect at the level of T4 was found 15-20 minutes. SPO2 were not significantly different among the three groups, but small changes of HR and BP among them. TAJ 2015; 28(1): 1-5